2017
DOI: 10.1080/08856257.2017.1297567
|View full text |Cite
|
Sign up to set email alerts
|

Study of an inclusive intervention programme in pictorial perception with blind and sighted students

Abstract: This study evaluates the effectiveness of an intervention programme administered to blind and sighted school students. The students were given information concerning style, author and technique of three paintings from three different artistic periods, as well as guidelines to assess the overall aesthetics of each image. This programme was administered to 28 participants: 7 totally blind (the entire population of blind students in Castilla-La Mancha) and 21 sighted peers. Several methods of accessibility, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The results regarding RQ2 show that the qualitative research method has been in great demand for the study of arts education for children with disabilities in the last ten years, followed by mix methods. ( Katušić & Burić, 2021), (Østergaard, 2019), (Nguyen Viet, et al, 2022), (Madrid-Manrique, 2020), (Erina et al, 2019), (Mehr et al, 2013), (Lian et al, 2020), (Bacon & Bennett, 2013), (Petsilas et al, 2019), (Carpio et al, 2017), (Shaughnessy, 2022), (Grosvenor & Pataki, 2017) 12…”
Section: Figure 5 Types Of Research Methodology Used In the Articlesmentioning
confidence: 99%
“…The results regarding RQ2 show that the qualitative research method has been in great demand for the study of arts education for children with disabilities in the last ten years, followed by mix methods. ( Katušić & Burić, 2021), (Østergaard, 2019), (Nguyen Viet, et al, 2022), (Madrid-Manrique, 2020), (Erina et al, 2019), (Mehr et al, 2013), (Lian et al, 2020), (Bacon & Bennett, 2013), (Petsilas et al, 2019), (Carpio et al, 2017), (Shaughnessy, 2022), (Grosvenor & Pataki, 2017) 12…”
Section: Figure 5 Types Of Research Methodology Used In the Articlesmentioning
confidence: 99%
“…The result demonstrated that the haptic memory ability is an age-related skill. Carpio et al [60] found that there is no significant difference between blind and sighted school students in content acquisition or aesthetic appreciation of images. This indicates that the blind people can experience the world through their haptic perception and eventually reach the same cognitive level of sighted people.…”
Section: Tactusmentioning
confidence: 99%
“…Children with visual impairments go through multifaceted troubles and hindrances in the development of adaptive functioning. They need to learn how to comprehend the physical world with a view to acquiring cognitive skills and realizing and discerning social relationships (van den Broek et al, 2017;Larsen & Dammeyer, 2021); although some researchers suggest that pedagogical approaches if familiar and available, work better and even almost equally for both normal and blind children (Carpio, Amérigo, & Durán, 2017). Marie-Laure comprehends the world with touches and mild marching of her fingers on the models of her neighborhood made by her father.…”
Section: Introductionmentioning
confidence: 99%